THE PSYCHOLOGICAL AND BEHAVIORAL INFLUENCE OF CHILDREN’S FICTION TO THE UPBRINGING OF A CHILD - Azimova Anora Saydulla qizi (Journals Park Publishing, 2022)
This article is devoted to describe the psychological and behavioral influence of children’s fiction to the upbringing of a child. “The Chronicles of Narnia” was selected as a bright example of upbringing child’s psychological and moral world. We can see some quotes or scenes taken from this novel, in which children can obtain the priceless knowledge.
Keywords: Children’s fiction; adventures; protagonist